Do analógico ao digital : análise do impacto da transição do sistema de TV aberta em Santo Antônio do Leverger - Silva Netto, Mérice da (2018)
The proposal of digital TV in Brazil provides that the population receive, throughout the national territory, image and sound with high quality compression standards. The parameter is the transition from the analogue system of transmission of image and sound to the digital transmission system for the open TV. The government, through Anatel, is responsible for dissemination to the whole society. This report records the range of information that the population of Santo Antonio do Lerverger has. This municipality of the state of Mato Grosso is part of the metropolitan region and is scheduled, on the schedule of the disconnection of the analogue signal, for November 28, 2018. The research was conducted in five neighborhoods of the urban area in households with beneficiaries of the Bolsa Program Family and other social programs of the federal government. The result of the analysis of the impact of the transition of the open TV system in Santo Antônio do Lerverger evidenced the misinformation in addition to that part of the population believed that it would run out of TV because it could not afford to buy another and part of it learned about the ", by research.